1992
DOI: 10.1016/0014-5793(92)80959-k
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an enzyme bound γ‐glutamyl acyl ester of carbamyl phosphate synthetase of Escherichia coli

Abstract: E. colt carbamyl phosphate synthetase binds 0.2-0.4 mol equivalents ofglutamine m an acid resmtant form. The bound material is quantitativdy released as glutamate by weak base hydroly~ib and as a mixture of 12% glutamate, 10% 7-glutamylhydroxamate, and 70% pyrrollidoneearboxylie acid by hydrolysis with hydroxylamilxe. These results provide direct evidence Ibr a 7-8lutamyl aeyl ester on the enzyme The absence of the aeyl ester in a mutant ¢arbamyl phosphate sYnthetase with a Cys ~-~ .-o Ser subshtut~on in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…All glutamineutilizing CPS II and Cps III contain Cys 301, His 385 and Glu 387 at the C-terminal GAT domain (Fig. 1), where the cysteine of the Cys-His-Glu triad carries out a nucleophilic attack on the amide carbonyl of glutamine to release ammonia (Chaparian and Evans 1991;Lusty 1992;Miles et al 1998;Thoden et al 1998 (Rubino et al 1986;Miran et al 1991;Huang and Raushel 1999), suggested that Cys and His functioned as a catalytic dyad for glutamine hydrolysis in the GAT site of Escherichia coli CPS (eCPS), whereas Glu of the GAT is not critical for eCPS activity. Non-glutamine-utilizing CPS I also share the two-domain GAT and four-domain SYN structure (Powers-Lee and Corina 1986; Marshall andFahien 1988, Rodriguez et al 1989) but they, with the exception of CPS I of R. catesbeiana, contain Ser 301, His 385 and Glu 387 at the C-terminal GAT domain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All glutamineutilizing CPS II and Cps III contain Cys 301, His 385 and Glu 387 at the C-terminal GAT domain (Fig. 1), where the cysteine of the Cys-His-Glu triad carries out a nucleophilic attack on the amide carbonyl of glutamine to release ammonia (Chaparian and Evans 1991;Lusty 1992;Miles et al 1998;Thoden et al 1998 (Rubino et al 1986;Miran et al 1991;Huang and Raushel 1999), suggested that Cys and His functioned as a catalytic dyad for glutamine hydrolysis in the GAT site of Escherichia coli CPS (eCPS), whereas Glu of the GAT is not critical for eCPS activity. Non-glutamine-utilizing CPS I also share the two-domain GAT and four-domain SYN structure (Powers-Lee and Corina 1986; Marshall andFahien 1988, Rodriguez et al 1989) but they, with the exception of CPS I of R. catesbeiana, contain Ser 301, His 385 and Glu 387 at the C-terminal GAT domain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…glycinamidine synthetase and the carbamoyl-P synthetase adducts could be attacked by exogenous ammonia to regenerate glutamine [36,39] and by hydroxylamine to release pyrrolidone carboxylic acid as k-glutamyl hydroxamate and its cyclic derivative [36,72]; the failure of carbamoyl-P synthetase mutant Cys269Ser to form such an adduct was indicative of catalytic Cys 269 involvement. Consistent with the absence of acceptor substrate in these experiments, the kinetic parameters for the formation of this adduct have been found close to those of carbamoyl-P synthetase glutaminase activity, showing that its hydrolysis is the glutaminase rate-limiting step [39].…”
Section: M-shmentioning
confidence: 99%
“…6) exhibits typical saturation kinetics, and when extrapolated to saturating ATP (Table II) showed a 12-fold increase in the GLNase activity. This coupling mechanism (26,54,55) ensures that the rate of glutamine hydrolysis matches the rate of production of carboxy phosphate.…”
Section: Construction and Expression Of The Recombinant Plasmids-mentioning
confidence: 99%